Sistem Informasi Pendataan Pegawai Dinas Peternakan Kabupaten Nabire Berbasis Website - Olvan Nadia Manikome; Kristia Yuliawan; Cici Kamalia (Jurnal Teknologi dan Informatika, 2024)
The Livestock Service Office playsan important role in livestock management and services in the Regency area. Its main mission is to ensure animal welfare, increase livestock productivity, control animal diseases, and manage other aspects related to livestock activities. However, data management still often relies on manual methods or the use of Microsoft Excel is deemed less effective and efficient. An information system is required to address this issue manage employee data quickly, accurately and can be updated easily. The research aims to design and execute a website-based information system for data collection for employee of the Nabire Regency Animal Husbandry Service. The research methods used include data collection through field studies, interview and literature studies, as well as system development using the Rapid Application Development (RAD) method. The results of this research include system design through Use Case Diagrams, Activity Diagrams, and user interfaces. System testing is conducted using the black box method method to ensure the system functions as expected. With the implementation of this system, it is hoped that employee data management at the Nabire Regency Livestock Service will become more efficient and accurate. This system makes it possible to carry out data collection, editing and deletion of employee data more easily and quickl. In conclusion, this system makes a significant contribution in improving operational efficiency and human resource management at the Nabire Regency Livestock Service.